Global DNA Methylation levels analysis in a serie of Hematological, Breast and Colorectal cancer samples from Argentina - Cerliani, María Belén (2019)
Unlike their normal counterparts, tumor cells exhibited highly variable CpG methylation levels in a large proportion of the genome, which can lead to malignant cell transformation through multiple pathways. This prompted us to assess the extent of LINE1 methylation, a surrogate marker of global DNA methylation, of samples derived from controls and cancer patients from Argentina. Preliminary DNA methylation results from selected samples were replicated in a large serie of 146 controls (blood) and various cancer types: 112 oncohematological cancer (HemCa), 70 colorectal cancer (CRC) and 68 breast cancer (BrCa) samples. Further, we evaluated correlation with biological, clinical and demographic features. Blood samples were available in all cases, and for solid tumors paired tumoral/non-tumoral adjacent tissues (T/N) were available too. LINE1 methylation level was analyzed by MS-MLPA method. HemCa cases showed statistically significant higher LINE1 methylation level (p>0.001) compared to controls (mean 0.93 and 0.84, respectively). This variation could be a consequence of chemotherapy. Methylation status in blood (0.86) and N tissue (0.87) from BrCa cases did not differ from controls, while levels in T tissue (0.88) were significantly higher than controls (p<0.05). No differences between N and T tissues were found. CRC cases showed hypomethylation for LINE1 when comparing T (0.81) to blood (0.87) or N tissues (0.88), reaching statistical significance of p<0.05 and p<0.001, respectively. This is in line with reported results. We found a negative correlation between individual age and methylation level in controls (-0.17, p=0.04), and BrCa T tissue (-0.33, p=0.03). Finally, no relevant associations between global methylation and mitochondrial genome variation (copy number and ancestry) were found for controls and HemCa sample sets. LINE1 methylation analysis in samples from lung, ovarian, pancreatic and skin cancers are ongoing.